La moneda de sal como don divino entre los ashaninka de la selva central del Perú - Rojas Zolezzi, Enrique (2025)
This article shows how the salt obtained by the ashaninka from the mine at the Cerro de la Sal and the salt obtained from springs along the ashaninka territory constitute a general equivalent as it is received from a divinity and a divine gift itself. This mythical conception give place to a system of exchange between ashaninka individuals that can transform along the generations in kinship relations between kindreds located in different valleys and interfluvial zones distant between them. The article also deals with the changes in this system because of the expansion of trading relations in the market and the changes in the institution of traditional exchange partners.